Hubungan antara Grit dengan Kesejahteraan Subjektif Pada Siswa Kelas XII yang Akan Melanjutkan Ke Perguruan Tinggi Negeri - Salsabila, Zahra; Wijaya, Erik (Innovative: Journal Of Social Science Research, 2025)
Education is the foundation for shaping high-quality individuals. At the high school level, education focuses more on preparing students to advance to higher education. Grit, or an individual’s determination to achieve long-term dreams, is an important component in supporting academic achievement and subjective well-being. Subjective well-being, which includes positive affect, negative affect, and global life satisfaction, also plays a crucial role in helping students face challenges and prepare for university entrance exams. This study aims to explore the relationship between grit and the subjective well-being of 12th -grade high school students planning to continue to state universities. The study involved 318 12th grade students as respondents, with details of 133 male students (41.8%) and 185 female students (58.2%). This research used a quantitative method with purposive sampling technique, utilizing the PANAS (Positive Affect and Negative Affect Scales) to measure subjective well-being and the grit scale to measure grit levels. The results of the main data analysis indicate a significant positive relationship, with r value of (318) = 0.273 and a p value of 0.000 < 0.05. It can be concluded that individuals with high grit levels are those who experience good subjective well-being.